Mitigating voltage and frequency fluctuation in microgrids using electric springs - Chen,X; Hou,Y; Tan,S-C; Lee,C-K; Hui,SYR (IEEE Transactions on Smart Grid, 2015)
Voltage and frequency fluctuation associated with renewable integration have been well identified by power system operators and planners. At the microgrid level, a novel device for the implementation of dynamic load response, which is known as the electric springs (ES), has been developed for mitigating both active and reactive power imbalances. In this paper, a comprehensive control strategy is proposed for ES to participate in both voltage and frequency response control. It adopts the phase angle and amplitude control which respectively adjust the active power and the reactive power of the system. The proposed control strategy is validated using a model established with power system computer aided design/electro-magnetic transient in dc system. Results from the case studies show that with appropriate setting and operating strategy, ES can mitigate the voltage and frequency fluctuation caused by wind speed fluctuation, load fluctuation, and generator tripping wherever it is installed in the microgrid.